The Sonic of Eclipse Panchromatic for Synthesizer and Percussion Ensemble - Tongkarnpanit, Panus; Permananda, Weerachat (Rangsit Music Journal, 2024)
This research article is part of dissertation in music : The Sonic Power of Eclipse Panchromatic for Synthesizer and Percussion Ensemble, which is a creative research of western music science that composed related to the solar and lunar eclipses, which emphasis on the rotation of the earth, moon and sun until the phenomenon of light and shadow happened in various forms, also including to the beliefs of the ancient Thai people who often understood that these two phenomena were bad prophetic, disaster, tragedy from where a god named “Rahu” who was a rage against the sun and the moon, therefore engulf the sun and the moon resulting in such a phenomenon. The researchers have characterized the importance of this phenomenon into 4 issues to create the music, including Darkness at noon: The Myth of the Solar, Penumbra: Light of the Shadow, Blood moon: The Blood Moonshine and Rahu: The Shadow God.